Microbiological profile of asymptomatic bacteriuria in pregnancy - Bose, Anu Mary; K., Sreekumary P.; Pulikkottil, Sobha Kurian (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Asymptomatic bacteriuria is the presence of actively multiplying bacteria within the urinary tract in the absence of any symptoms. Anatomical and physiological changes make women more susceptible to UTI in pregnancy. The objective of present study was to determine the percentage of pregnant women with asymptomatic bacteriuria and its microbiological profile. Methods: A total of 555 antenatal women who had no clinical features of urinary tract infection were recruited for this study over a period of one year. Clean catch mid-stream urine sample was collected and semi quantitatively cultured immediately. Significant bacteriuria was identified and antibiotic sensitivity found out by conventional methods. Results: Significant growth was observed in 26 samples. There was no association between age, parity, gravidity, period of gestation and asymptomatic bacteriuria. Gram stain was found to be the best screening test. Escherichia coli were the commonest organism isolated. Escherichia coli and Staphylococcus saprophyticus were the most resistant organisms. Conclusions: Escherichia coli, the most common organism isolated, was resistant to most of the commonly used antibiotics. Wet film examination, the most commonly used screening test in our set up, was less sensitive and specific. So culture has to be done in all antenatal cases for screening asymptomatic bacteriuria of pregnancy.